A three-dimensional conductive molecularly imprinted electrochemical sensor based on MOF derived porous carbon/carbon nanotubes composites and prussian blue nanocubes mediated amplification for chiral analysis of cysteine enantiomers. (10th April 2019) - Duan, Dingding; Yang, Hua; Ding, Yaping; Li, Li; Ma, Guohong
Abstract: A highly sensitive and selective molecular imprinting polymer (MIP) sensor was fabricated based on prussian blue (PB)-porous carbon (PC)-CNTs hybrids modified glassy carbon electrode (GCE) for enantioselective recognition of cysteine enantiomers. We prepared a conductive polypyrrole (PPy) MIPs by convenient electropolymerization methods and the elution of templates was performed by a simple overoxidation/dedoping process. The physical properties of materials and the modified sensors were investigated by using X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) and transmission electron microscopy (TEM). Cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscope (EIS) were used to assess the electrochemical performance of the sensors. Under optimal conditions, the resulted 3D porous conductive sensor was used to enantioselective recognition L-/D-cysteine respectively, with a linear detection range from 10 −13 to 10 −7  mol L −1 . Furthermore, good reproducibility, long-term stability, favorable selectivity was achieved in the experiment and the MIECS was successfully applied to detect cysteine in human serum with high recovery.